ANALISIS IMPLEMENTASI HUKUM EKONOMI ISLAM TERHADAP PRAKTIK JUAL BELI TAHU DAN TEMPE DI DESA LAOK JANG-JANG KANGEAN SUMENEP - listriyati, listriyati; berkah, dian (Universitas Muhammadiyah Surabaya, 2020)
To know and tempeh trade that takes place in Laok Jang-Jang Kangean village has been practiced according to the habits that have been in place for a long time in the community. But Islam regulates its people on how to transact well between each other. All the work done should not go out of the way, so that no one feels harmed and no one feels remorse in the future. The problem in this study is how the trading practice system. To know and tempeh in Laok Jang-Jang KangeanSumenep Village and how to Implement Islamic Economic Law in Laok Jang-Jang KangeanSumenep Village. The purpose of this research is to uncover the problem of The Implementation analysis of Islamic Economic Law AgainstTempe To know-selling practices in Laok Jang KangeanSumenep Village.This research is field reseach that is analyzed using a qualitative descriptive approach. Samples are taken using total sampling that all sellers and buyers know and tempe so that this problem can be presented clearly, the research instruments used are interviews, observations and documentation. Data analysis is done through three steps, namely data reduction, data presentation, and withdrawal of conclusions or verification. Â Based on research, it is known that the practice of buying and selling toy and tempeh that occurs in the villagers of Laok Jang-Jang KangeanSumenep. it has become a tradition where in trade transactions know and tempe that often only use purchase receipts even some are only by oral.Key Words:Islamic Economic System, Against Buying and Selling Practices